Centrifugal projections to the main olfactory bulb revealed by transsynaptic retrograde tracing in mice. Issue 11 (26th January 2020) - Schneider, Nanette Y.; Chaudy, Sylvie; Epstein, Alberto L.; Viollet, Cécile; Benani, Alexandre; Pénicaud, Luc; Grosmaître, Xavier; Datiche, Frédérique; Gascuel, Jean
Abstract: A wide range of evidence indicates that olfactory perception is strongly involved in food intake. However, the polysynaptic circuitry linking the brain areas involved in feeding behavior to the olfactory regions is not well known. The aim of this article was to examine such circuits. Thus, we described, using hodological tools such as transsynaptic viruses (PRV152) transported in a retrograde manner, the long‐distance indirect projections (two to three synapses) onto the main olfactory bulb (MOB). The ß‐subunit of the cholera toxin which is a monosynaptic retrograde tracer was used as a control to be able to differentiate between direct and indirect projections. Our tracing experiments showed that the arcuate nucleus of the hypothalamus, as a major site for regulation of food intake, sends only very indirect projections onto the MOB. Indirect projections to MOB also originate from the solitary nucleus which is involved in energy homeostasis. Other indirect projections have been evidenced in areas of the reward circuit such as VTA and accumbens nucleus. In contrast, direct projections to the MOB arise from melanin‐concentrating hormone and orexin neurons in the lateral hypothalamus. Functional significances of these projections are discussed in relation to the role of food odors in feeding and reward‐related behavior. Abstract : Retrograde transsynaptic virus (a) allowed to trace (two to three synapses) projections onto the main olfactory bulb (b). Monosynaptic cholera toxin b (a) was a control to differentiate direct and indirect projections. The MOB mainly receives indirect projections from hypothalamic nuclei (c) and reward‐related regions (c1), underlining the role of olfaction in feeding (d).